Unsteady bending function for an unlimited anisotropic plate - Alexander O. Serdiuk; Dmitry O. Serdiuk; Grigory V. Fedotenkov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2021)
This work is devoted to the study of non-stationary vibrations of a thin anisotropic unbounded Kirchhoff plate under the influence of random non-stationary loads.